Calling on the community understanding participation in the heritage sector, an interactive governance perspective - Rodenberg, Jeroen; Wagenaar, Pieter 1967-; Burgers, Gert-Jan 1961- (Berghahn, 2023)
"There is a call in Heritage Studies to democratize heritage practices and place local communities at the forefront; heritage plays an important role in identity formation, and therefore in social inclusion and exclusion. Public participation is often presented as the primary means to prioritize communities. Studies focusing on public participation are typically descriptive in nature, however these studies lack a strong analytical framework that enables us to understand participation. This series of studies contributes to a better understanding of public participation in the heritage sector by applying Public Administration theory on collaborative governance"--
Keywords: Lokales Wissen; Partizipation; Forschungsmethode; Kulturerbe; Cultural property / Protection / Case studies; Cultural property / Protection / Citizen participation / Case studies; Archaeology and state / Case studies; Art and state / Case studies; Public administration / Case studies; Archaeology and state; Art and state; Cultural property / Protection; Cultural property / Protection / Citizen participation; Public administration; Case studies; Aufsatzsammlung